New topology of direct current claw-pole machines for stop-start application. Issue 5 (15th August 2018) - Bazhar, Sara; Ristagno, Baptiste; Fontchastagner, Julien; Takorabet, Noureddine; Labbe, Nicolas
Abstract : Purpose: This paper aims to propose a new topology of direct current (DC) machine using claw-pole stator to replace standard DC starter in micro-hybrid vehicles. The main interest of such a topology is the reduction of copper volume. Design/methodology/approach: The design of the claw-pole machine is based on a multi-objective optimization of several topologies, based on a three-dimensional (3D) reluctance network modeling. The 3D finite element (FE) model is used to check the results of the optimization, and a prototype is manufactured and tested with satisfactory results. Findings: The claw-pole topology with wave-shape windings allows to replace the current DC series classical starter because of to its copper volume saving. Research limitations/implications: This model is only limited to the optimization of the claw-pole stator for a fixed geometry of the rotor. Practical implications: The research outcome shows that claw-pole machine can replace the series-excited DC machines of starters and at the same time achieve the same performance at reduced copper volume. Originality/value: The paper deals with a new DC machine topology to reduce the copper volume through the suppression of the classical stator end-windings. The use of Claw-Pole inductors ensures this copper reduction.